Menimbang Kekuatan Hukum Antara Wasiat dan Waris Menurut Madzhab Imam Syafi’i - Kamelia, Nabila Rizka; Mukarrom, Azmil (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyze and find out how the legal force between wills and inheritance according to the perspective of the Imam Shafi'i madzhab. The Shafi'i Madhhab asserts that there is a fundamental difference between these two concepts, although both relate to the inheritance of property. An heir is the beneficiary of the beneficiary of the testator's property according to Islamic law, whereas a will gives the testator the right to divide their property according to their own will. To describe the problem or the formulation of the problem, researchers use qualitative methods with a phenomenological approach in the frame of the theory of testamentary law and the theory of inheritance law in Islam. The result of the study is that according to the Madzhab of Imam Shafi'i the law of wills is stronger than inheritance. Imam Shafi'i argues that the legal power of a will is stronger because in a will, one can distribute their property more flexibly and according to their personal will, as long as it does not violate the restrictions set in religion.